Jurnalistik Islam: Kajian Kode Etik Perspektif Islam - Muttaqin; Moh. Husnul Affan (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
The code of ethics is a guide that every work professional must own. Even in the world of journalism, there is a code of ethics that all journalists should obey. This code of ethics was created and designed by experts from various institutions and boards with various considerations. However, it turns out that the code of ethics that has been made and designed well has not been complied groups. How can this happen? While this code of ethics is the main guideline for a journalist. According to Islam, this is allegedly due to the loss of adab of a journalist. For this reason, this article will discuss the akhlak of a journalist, especially Muslim. In addition, Islam also conception the type of news that a Muslim journalist should convey.